Factors influencing management of procurement records in Tanzania: A survey of selected procuring entities - Mohamed, Bakari Maligwa (Mzumbe University, 2024)
A Thesis Submitted in Fulfilment of the Requirements for Award of the Degree of Doctor of Philosophy of Mzumbe University, 2019